2021
DOI: 10.1097/dss.0000000000003179
|View full text |Cite
|
Sign up to set email alerts
|

Survey of Dermatologic Procedures in Transgender Adults

Abstract: BACKGROUND Dermatologists have the opportunity to provide medically necessary procedures, including laser hair removal, to transgender patients for gender affirmation. Further research is required to better assess the unique dermatologic needs of this population. OBJECTIVE To examine the prevalence of dermatologic procedures among transgender people in the context of gender-affirming treatment. METHODS This … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 26 publications
1
7
0
Order By: Relevance
“…4 Yet, a cross-sectional study found that 7.5% of transmasculine and 65% of transfeminine persons had received gender-affirming dermatologic procedures in the past. 3 The present study identifies new reasons for implementing formalized MIGAP training, including that most dermatology residents desire such training and that more education hours is associated with a greater comfort level. It also reveals a critical gap in hands-on training of these procedures, a key factor in success, even beyond the specific patient population the authors studied.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…4 Yet, a cross-sectional study found that 7.5% of transmasculine and 65% of transfeminine persons had received gender-affirming dermatologic procedures in the past. 3 The present study identifies new reasons for implementing formalized MIGAP training, including that most dermatology residents desire such training and that more education hours is associated with a greater comfort level. It also reveals a critical gap in hands-on training of these procedures, a key factor in success, even beyond the specific patient population the authors studied.…”
Section: Discussionmentioning
confidence: 88%
“…These treatments can improve quality of life and support the psychological well-being of this historically marginalized group. 2,3 Despite this increase in openly transgender patients, there are currently no MIGAP requirements for trainee education from the Accreditation Council for Graduate Medical Education. A recent study of program directors across multiple specialties found that less than one-half of trainees who receive exposure to minimally invasive procedures are specifically exposed to MIGAPs.…”
mentioning
confidence: 99%
“…11,12 In those with gender identities different from their sex assigned at birth, hair modification plays an important role in gender expression and concordance. 13,14 Recently, social media movements have championed defying traditional beauty standards and embracing natural hair. 15 A notable example is found in women with PCOS who have reclaimed their beards.…”
Section: Historical Perspectivesmentioning
confidence: 99%
“…94,95 More recently, laser hair removal has been proven to play a large role in the spectrum of gender-affirming procedures, particularly in neo-vaginoplasty grafts and feminization of hair patterns in transwomen. 13,96 One study showed that elective hair removal in transwomen is associated with increased subjective well-being. 14…”
Section: Ethical Framework For Hair Removal In Pediatric Patientsmentioning
confidence: 99%
“…This may be due to their greater use of dermatologic procedures compared to transmasculine individuals. 49 Furthermore, gender-affirming dermatology treatments may be more desirable for transfeminine individuals, as transgender women prioritize facial changes while transgender men prioritize chest modifications. 50 Considering that more gender-affirming dermatology treatments apply to the face, this may help to explain the imbalance.…”
Section: Study Populationsmentioning
confidence: 99%